(3GdUMGM aj GddZIs - (3ESeGYjd Hf MeGO GdLhgQj , CHh fUQ, J (B393 (3g` s ((3eXaQ Hf eMehO Hf CHj GdbGSe GdGQOHjdi s)
(3ChdgG (B:s
(3jHJOF H(B( (3LXX (B) s
(3BNQgG (B:s
(3jfJgi H (B( (3gja (B) s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B267s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1071s
Keywords: (3GddZIs